PETA PERSAINGAN PRODUK KARTU SELULER BERDASARKAN SEGMEN KONSUMEN - Nur Indrianti; Yunto Satrio (Universitas Ahmad Dahlan Indonesia, 2013)
One cannot deny the fact that cellular phones happen to be one of the most sought after and popular gadgets all over the world including Indonesia. With the quick development in technology, cellular phones are surely becoming more and more popular with each passing day. Subscriber Identity Module (SIM) Cards are used with carriers that operate on the Global System for Mobile Communication (GSM) network. The rapidly increasing demand for cellular phones indeed drives demand for SIM cards, resulting in the competitiveness of SIM card providers. This competition drives innovation in product development as well as in customer services. With regards to the increasing competitiveness of SIM card market, this study deals with market analysis of SIM cards. The analysis was based on the sample of cellular phone customers from Yogyakarta Special Region. The objective of the study is to identify market share of each SIM card and the factors to be considered by consumer when purchasing a SIM card. We use segmentation approach to analyse the competition among SIM card products. The result of the study shows that there is tight competition between Simpati and IM3 SIM cards in almost all segmens. Based on the analysis, we suggest Simpati to compete in segmen 1 that prioritizes a wide range of signal, while IM3 in segmen 3 that prioritizes strong signal. Key words: SIM card, market analysis, segmentation, Simpati, IM3 I. PENDAHULUAN